Variant Analysis of Alkaptonuria Families with Significant Founder Effect in Jordan. (11th March 2021) - Khalil, Raida; Ali, Dema; Mwafi, Nesrin; Alsaraireh, Arwa; Obeidat, Loiy; Albsoul, Eman; Al Sbou', Ibrahim
Abstract : Background . Metabolic disorder alkaptonuria is an autosomal recessive disorder caused by mutations in the HGD gene, and a deficiency HGD enzyme activity results in an accumulation of homogentisic acid (HGA), ochronosis, and destruction of connective tissue. Methods . We clinically evaluated 18 alkaptonuria patients (age range, 3 to 60 years) from four unrelated families. Furthermore, 11 out of 18 alkaptonuria patients and 7 unaffected members were enrolled for molecular investigations by utilizing Sanger sequencing to identify variants of the 14 exons of HGD gene. Results . We found that the seven patients from the 4 unrelated families carried a recurrent pathogenic missense variant (c.365C>T, p. Ala122Val) in exon 6 of HGD gene. The variant was fully segregated with the disease in affected family members while the other unaffected family members were heterozygous carriers for this variant. Additionally, the clinical features were fully predicted with alkaptonuria disorder. Conclusion . In this study, we confirmed that the most common variants in Jordanian AKU patients was c.365C>T, p. Ala122Val in exon 6 of HGD gene. Additionally, we correlated the clinical and genetic features of AKU patients at various ages (3-60 years).